2018
DOI: 10.9734/jemt/2019/44943
|View full text |Cite
|
Sign up to set email alerts
|

Are the Determinants of Imports Similar Across Manufactured Products? Evidence from Nigeria

Abstract: The study investigates the determinants of selected manufactured imports in Nigeria with a special focus on the role of domestic production. The autoregressive distributed lag (ARDL) in the context of new trade theory was utilised with data coverage between 1985 and 2016. Results show that imports of various manufactured products are affected differently by some factors. In particular, domestic output of electrical & electronics have a significant and negative effect on own imports. However, there was no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…This empirical finding implies that changes in the exchange rate significantly affect the performance of imports in the ASEAN Economic Community countries. This condition is related to multinational companies operating in these ASEAN countries, whose production components still have to be imported (Olubiyi et al, 2019;Mwangi, 2020;Lubik, 2014).…”
Section: Empirical Findings and Resultsmentioning
confidence: 99%
“…This empirical finding implies that changes in the exchange rate significantly affect the performance of imports in the ASEAN Economic Community countries. This condition is related to multinational companies operating in these ASEAN countries, whose production components still have to be imported (Olubiyi et al, 2019;Mwangi, 2020;Lubik, 2014).…”
Section: Empirical Findings and Resultsmentioning
confidence: 99%
“…Another study for Indonesia by Solikin and Nizar (2023) employed the vector autoregressive (VAR) technique and submitted that government revenue and tax revenue significantly and positively affected public spending. Olubiyi and Ibironke (2023) also showed for Nigeria that asymmetric exchange and inflation rates, tax and oil revenue impacted government outlay. Mirovic et al (2023) conducted a study for the Serbian economy using the ARDL model and found that government revenue and inflation rate substantially affect public spending.…”
Section: Empirical Reviewmentioning
confidence: 98%